Biology and harmfulness of Brassica pod midge (Dasineura brassicae Winn.) in winter oilseed rape (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
The Brassica pod midge (Dasineura brassicae Winn.) is an important pest in oilseed rape (Brasica napus L.). It develops two generations per year and overwinters in the larval stage in cocoons in soil. Immigration of the first generation adults lasted from the beginning of April until the end of May. Larvae developed in pods from mid-April to mid-June, causing pod deformation and cracking, which resulted in premature falling out of seeds and yield reduction. Pod damage amounted to 11.6%. The emergence of the second generation adults was detected at the end of May and in the first ten days of June. D. brassicae was found to lay eggs in healthy pods and no correlation was found with the cabbage seed weevil, Ceutorhynchus assimilis Paykull.
Keywords: Brassica pod midge; Oilseed rape; Life cycle